The development of web-based supervisor-supervisee assigning system using rule-based algorithm - Yeoh, Chien Din (Universiti Malaysia Sarawak (UNIMAS), 2017)
year project is a crucial coursework, as it is the indicator of a student's ability to apply the knowledge acquired throughout their years of studies in their project. In Faculty of Cognitive Sciences and Human Resources, UNIMAS, all final year students are assigned with at least one supervisor to inspect their FYP. Approximately 200 students are assigned with supervisors by Cognitive Sciences coordinator in year 2016. The assigning task is shown to be time taking, and should be enhanced. Therefore, this research project developed a web-based Supervisor-supervisee Assigning System that can automate the coordinator’s assigning task. The Supervisor-supervisee Assigning System is developed with PHP together with Laravel Framework and MySQL. And Unified Theory of Acceptance and Use of Technology (UTAUT) is used to evaluate the acceptance of this new system. The application system is accessible through World Wide Web, so final year students can update their information online. Coordinator can receive an assigned list of supervisee in seconds through the online system. In the following chapters, the overview of the system architecture, system design, system development and summarized evaluation result are discussed in detail.